Mechanism of Inhibition of Inflammation in Osteoarthritis by Tougu Xiaotong Capsule via Regulating Ras-Raf-MEK1/2-ERK1/2 Signaling Pathway - Munan LIN; Xiang SHAO; Limei XU; Xin ZHANG; Zaishi ZHU; Yidan HAN; Xinwei DUAN; Jianmei CHEN; song GAO; Xihai LI (康复学报)
Objective:To investigate the mechanism of inhibition of inflammation in osteoarthritis by Tougu Xiaotong capsule(TXC)via regulating Ras-Raf-MEK1/2-ERK1/2 signaling pathways.Methods:The chondrocytes from 4-week-old SD male rats obtained by the mechanical typeⅡcollagenase digestion method were cultured in vitro and identified by typeⅡcollagen immunohistochemical staining. Isolated chondrocytes of passage two were divided into blank group, model group(treatment with 10 ng/mL of LPS for 8 h), inhibitor group(treatment with 10 ng/mL of U0126 for 30 min followed by 10 ng/mL of LPS for additional 8 h)and TXC group(treatment with 10 ng/mL of LPS plus 300 μg/mL of TXC for 8 h).Western blot was carried out to detect the expression of Ras, Raf, p-ERK1/2, MEK1/2, MMP-3 and MMP-13.qPCR was used to detect the mRNAs expression of MEK1/2, ERK1/2, MMP-3 and MMP-13, as well as the expression of miR-27b, miR-34a and miR-146a.Results:1)The cytoplasm of isolated cells(P2)from the cartilage of knee joint of 4-week-old SD male rats was stained brown by typeⅡcollagen immunohistochemical staining as compared with the negative control cells, which indicated that the extracted cells were chondrocytes.2)The expression of Ras, Raf, MEK1/2, MMP-3, MMP-13 in the model group was significantly higher than that in the blank group, respectively(P<0.01, P<0.05), but the expression of p-ERK1/2 had no significant difference(P>0.05);the expression of Ras, Raf, p-ERK1/2, MEK1/2, MMP-3, MMP-13 in both the inhibitor group and the TXC group was lower than that in the model group, respectively(P<0.01, P<0.05), but the expression of MEK1/2 in the TXC group had no significant difference compared to that in the model group(P>0.05).3)The mRNA expression of MEK1/2, ERK1/2, MMP-3 and MMP-13 in the model group was significantly higher than that in the blank group, respectively(P<0.01);their expression in both the inhibitor group and the TXC group was lower than that in the model group, respectively(P<0.01, P<0.05).4)The expression of miR-27b in the model group was significantly lower than that in the blank group(P<0.01), but its expre-ssion in both the inhibitor group and the TXC group was higher than that in the model group(P<0.01);the expression of both miR-34a and miR-146a in the model group was significantly higher than that in the blank group, respectively(P<0.01, P<0.05);however, their expression in both the inhibitor group and the TXC group was lower than that in the model group, respectively(P<0.01, P<0.05).Conclusion:Tougu Xiaotong capsule regulates the expression of key factors in Ras-Raf-MEK1/2-ERK1/2 signaling pathway and miR-27b, miR-34a and miR-146a to regulate the inflammatory of chondrocytes, thereby inhibiting osteoarthritis inflammation and protecting articular cartilage.